Literature, Philosophy, Nihilism - Weller, Shane. author. aut Link
X, 234 p.
Keywords: This book charts the history of the concept of nihilism in some of the most important philosophers and literary theorists of the modern and postmodern periods, including Heidegger, Adorno, Blanchot, Derrida, and Vattimo. Weller offers the first in-depth analysis of nihilism's key role in the thinking of the aesthetic since Nietzsche.